AB0315 Frequency of Radiographic Procedures in Patients with Rheumatoid Arthritis. (10th June 2014) - Venegas Pont, M.; Crowson, C.S.; Gabriel, S.E.; Davis, J.M.; Matteson, E.L.
Abstract : Background: Patients with rheumatoid arthritis (RA) undergo radiographic investigations for disease and comorbidity evaluation. Indeed, the presence of radiographic changes in joints can be diagnostic for RA. The actual use of radiographic imaging in RA is unknown. Objectives: To assess the use of imaging in RA, and assess the number and frequency of radiographic imaging studies in patients with RA versus patients without RA. Methods: Study subjects were from a previously assembled population-based cohort in Olmsted County, MN, USA who fulfilled 1987 ACR criteria for RA in 1988-2007, as well as a previously identified comparison cohort of patients without RA of similar age and sex. The total number of radiographic procedures, the total person-years (py) of follow-up, the number and rates of radiographic images by anatomic sites as well as number and rate of DEXA and radionuclide bone imaging were assessed. Results: 650 patients with RA and 650 patients without RA were included (mean age 55.8 years; 69% female in both cohorts). A total of 27088 radiographic procedures were performed among patients with RA and 21006 among non-RA subjects during a total of 7358 and 7597 person-years [py] of follow-up, respectively. RA patients had significantly more chest, upper extremity (UE), lower extremity (LE), bone and DEXA imaging (Table). Patients with RA also had significantly more radiographs of the spine, hip, pelvis, and sacroiliac joints (not shown). Patients with positive rheumatoid factor (RF) had more radiographic procedures than those with negative RF. Women underwent more procedures than men (Table). 57% of patients underwent hand/wrist radiographs within 1 year after RA diagnosis, but this declined to 42% during 1-3 years after diagnosis, 32% during 3-5 years after diagnosis and 28% beyond 5 years after diagnosis. The rate of utilization of hand radiographs peaked in 2001 at 45 x-rays per 100 py and subsequently declined steadily to 17 per 100 py in 2011. The rate of utilization of hand radiographs was significantly higher among women than men prior to 2002, but the rates of utilization of hand radiographs were similar in both sexes subsequently. Conclusions: Patients with RA undergo significantly more radiographic procedures than persons without RA, particularly of the hands/wrist and feet. Hand X-rays are less frequently obtained in recent years, possibly reflecting clinical perception of less need due to better therapies, and lower rates of hand surgeries 1 .DEXA and radionuclide bone scans are more frequently done in patients with RA, likely in assessment of diagnosis and comorbidities. RF+ patients underwent more scans than RF- patients, possibly due to more severe disease in patients with positive RF. References: Shourt C et al. J Rheumatol 39(3):481-5, 2012 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1573